MANAJEMEN EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMK PGRI MUARADUA OKU SELATAN - Heri Kiswanto (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the management of Islamic Religious Education (PAI) learning evaluation at SMK PGRI Muaradua, OKU Selatan Regency. Learning evaluation is an essential component of the educational process that helps measure the effectiveness of learning and student competency achievement. This research uses a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation. The results of the study indicate that the management of PAI learning evaluation at SMK PGRI Muaradua involves several stages: planning, implementation, and follow-up. In the planning stage, teachers prepare an evaluation plan that includes objectives, materials, methods, and evaluation tools. Evaluation implementation is carried out through various forms, such as written, oral, and practical tests. Follow-up evaluation includes analyzing evaluation results, providing feedback to students, and improving teaching methods. The challenges faced in managing PAI learning evaluation at this school include limited time, inadequate facilities and infrastructure, and variability in student abilities. Nevertheless, continuous improvement efforts are made, such as enhancing teacher competencies through training and workshops, and optimizing the use of technology in learning evaluation. This study provides recommendations to improve the quality of PAI learning evaluation management at SMK PGRI Muaradua, including strengthening collaboration between teachers, students, and parents, as well as developing a more comprehensive and sustainable evaluation system.